Malawi and Millennium Development Goal 4: a Countdown to 2015 country case study. Issue 3 (March 2016) - Kanyuka, Mercy; Ndawala, Jameson; Mleme, Tiope; Chisesa, Lusungu; Makwemba, Medson; Amouzou, Agbessi; Borghi, Josephine; Daire, Judith; Ferrabee, Rufus; Hazel, Elizabeth; Heidkamp, Rebecca; Hill, Kenneth; et al.
Summary: Background: Several years in advance of the 2015 endpoint for the Millennium Development Goals (MDGs), Malawi was already thought to be one of the few countries in sub-Saharan Africa likely to meet the MDG 4 target of reducing under-5 mortality by two-thirds between 1990 and 2015. Countdown to 2015 therefore selected the Malawi National Statistical Office to lead an in-depth country case study, aimed mainly at explaining the country's success in improving child survival. Methods: We estimated child and neonatal mortality for the years 2000–14 using five district-representative household surveys. The study included recalculation of coverage indicators for that period, and used the Lives Saved Tool (LiST) to attribute the child lives saved in the years from 2000 to 2013 to various interventions. We documented the adoption and implementation of policies and programmes affecting the health of women and children, and developed estimates of financing. Findings: The estimated mortality rate in children younger than 5 years declined substantially in the study period, from 247 deaths (90% CI 234–262) per 1000 livebirths in 1990 to 71 deaths (58–83) in 2013, with an annual rate of decline of 5·4%. The most rapid mortality decline occurred in the 1–59 months age group; neonatal mortality declined more slowly (from 50 to 23 deaths per 1000 livebirths), representing an annual rate of decline of 3·3%. Nearly half of the coverage indicators have increased by more than 20 percentage points between 2000 and 2014. Results from the LiST analysis show that about 280 000 children's lives were saved between 2000 and 2013, attributable to interventions including treatment for diarrhoea, pneumonia, and malaria (23%), insecticide-treated bednets (20%), vaccines (17%), reductions in wasting (11%) and stunting (9%), facility birth care (7%), and prevention and treatment of HIV (7%). The amount of funding allocated to the health sector has increased substantially, particularly to child health and HIV and from external sources, but remains below internationally agreed targets. Key policies to address the major causes of child mortality and deliver high-impact interventions at scale throughout Malawi began in the late 1990s and intensified in the latter half of the 2000s and into the 2010s, backed by health-sector-wide policies to improve women's and children's health. Interpretation: This case study confirmed that Malawi had achieved MDG 4 for child survival by 2013. Our findings suggest that this was achieved mainly through the scale-up of interventions that are effective against the major causes of child deaths (malaria, pneumonia, and diarrhoea), programmes to reduce child undernutrition and mother-to-child transmission of HIV, and some improvements in the quality of care provided around birth. The Government of Malawi was among the first in sub-Saharan Africa to adopt evidence-based policies and implement programmes at scale to prevent unnecessary child deaths. Much remains to be done, building on this success and extending it to higher proportions of the population and targeting continued high neonatal mortality rates. Funding: Bill & Melinda Gates Foundation, WHO, The World Bank, Government of Australia, Government of Canada, Government of Norway, Government of Sweden, Government of the UK, and UNICEF.